Resveratrol prevents the expression of glaucoma markers induced by chronic oxidative stress in trabecular meshwork cells - Luna, Coralia (2008)
Elevated intraocular pressure (IOP) constitutes the best characterized risk for primary open-angle glaucoma (POAG). Elevated IOP is believed to result from an increase in aqueous humor outflow resistance at the level of the trabecular meshwork (TM)/ Schlemm's canal (SC). Malfunction of the TM in POAG is associated with the expression of markers for inflammation, cellular senescence, oxidative damage, and decreased cellularity. Current POAG treatments rely on lowering IOP, but there is no therapeutic approach available to delay the loss of function of the TM in POAG patients. We evaluated the effects of chronic administration of the dietary supplement resveratrol on the expression of markers for inflammation, oxidative damage, and cellular senescence in primary TM cells subjected to chronic oxidative stress (40% O(2)). Resveratrol treatment effectively prevented increased production of intracellular reactive oxygen species (iROS) and inflammatory markers (IL1α, IL6, IL8, and ELAM-1), and reduced expression of the senescence markers sa-β-gal, lipofuscin, and accumulation of carbonylated proteins. Furthermore, resveratrol exerted antiapoptotic effects that were not associated with a decrease in cell proliferation. These results suggest that resveratrol could potentially have a role in preventing the TM tissue abnormalities observed in POAG.